A COMPETITIVE ADVANTAGE REVIEWED BY MARKET ORIENTATION, PRODUCT INNOVATION AND INNOVATIVE WORK BEHAVIOR IN SMEs TOWARDED RUMAH BUMN PURWOKERTO - Sari, Kartika Dwi Chandra; Putri, Puspita Lianti (LPPM Universitas Harapan Bangsa, 2022)
The needs of Micro, Small and Medium Enterprises (MSMEs) in developing competitive advantage will determine the sustainability of a business. One important thing that needs to be considered by MSMEs is the competitive advantage that each business has. Excellence is the result of the implementation of value creation that is not capable of being created by the efforts of potential competitors. The need for MSMEs in creating competitive advantage can be seen through market orientation, product innovation, and innovative work behavior. The research population was all SMEs assisted by Rumah BUMN Purwokerto with a sample of 54 business units. The study uses the Multiple Regression Hypothesis Test accompanied by classical assumption tests and instrument tests. For MSME actors assisted by Rumah BUMN Purwokerto, it was found that product innovation, market orientation and innovative work behavior have a positive effect on competitive advantage.